Industrial policy, innovation, and complexity comparative analysis, trends, and prospects - Varsakelis, Nikolaos 1959-; Varsakelis, Nikolaos 1959-; Zarotiadis, Grigorios 1972-; Zarotiadis, Grigorios 1972-; Tzouvelekas, Manolis D. 1972-; Tzouvelekas, Manolis D. 1972- (IGI Global Scientific Publishing, 2026)
"This book aims to bring together diverse perspectives and in-depth analyses from scholars, policymakers, and practitioners on the current state and future directions of industrial policy in complex economies"-- Provided by publisher.
Includes bibliographic references and index. - Description based on title screen (IGI Global, viewed 08/11/2025)
Keywords: Industrial policy -- History -- 21st century.; Industries -- History -- 21st century.; Cohesion Policy; Economic Development; Economic Resilience; Global Value Chains; Industrial Policy; Innovation Policy; Innovative Strategies; Public Health Security; Public Policy; Sustainable Growth; Technological Transformations